Pattern Recognition in Musculoskeletal Imaging Using Artificial Intelligence - Gorelik, Natalia; Chong, Jaron; Lin, Dana J. (Seminars in Musculoskeletal Radiology, 2020)
Artificial intelligence (AI) has the potential to affect every step of the radiology workflow, but the AI application that has received the most press in recent years is image interpretation, with numerous articles describing how AI can help detect and characterize abnormalities as well as monitor disease response. Many AI-based image interpretation tasks for musculoskeletal (MSK) pathologies have been studied, including the diagnosis of bone tumors, detection of osseous metastases, assessment of bone age, identification of fractures, and detection and grading of osteoarthritis. This article explores the applications of AI for image interpretation of MSK pathologies.
Keywords: musculoskeletal; deep learning; neural network